Performance indicators and competition ranking in Women`s and Men`s World Handball Championship 2017 - Noutsos, S. K.; Rousanoglou, N. E.; Meletakos, G. P.; Bayios, A. I.; Boudolos, D. K. (Journal of Physical Education and Sport, 2018)
The study aims to evaluate the efficacy of specific performance indicators in the final competition ranking of national handball teams, of different competitive levels on a world scale. Also, an attempt was made to portray to what degree the examined performance indicators influence game performance. Additionally, an attempt was made to clarify to what degree the observed indices affect the final ranking. The collected data comprised eight indices: a) Age (years) b) Body Height (cm) c) Body Mass (kg) d) International Matches played e) International Goals scored f) Total Shots per player g) Total goals per player h) Team Scoring Efficiency (%). These indices were grouped into: i) Anthropometric index that includes, a) Body Height (cm) b) Body Mass (kg) (ii) Game experience indices that include a) Age (years) b) International Matches played c) International Goals scored, (iii) Performance efficacy indices that include a) Total Shots per player b) Total goals per player c) Team Scoring Efficiency (%). Descriptive statistics were used (mean, standard deviation), a comparison between the group with ONE-WAY-ANOVA followed by non-parametric correlation Spearman`s rho and Factor analysis. Placing the indices in order of hierarchy by our results, the most critical parameters in the ranking of the men's teams is game experience and anthropometric index that influence the final team ranking. As far as the women's groups are concerned, the index that played a vital role and affects the final ranking, in order of importance, are performance efficacy, game experience indices, follow anthropometrically and finally Team Scoring Efficiency